Bread production technology modelling using hop starter in ovens of various types - V. A. Bukhovets; T. V. Kirillova; N. A. Fokina; I. V. Romanov (Новые технологии, 2020)
The article studies the processes of structure formation of baked dough pieces using wheat and hop starters and changes in the properties of finished products and semi-finished products depending on the baking methods. A whole complex of physical, chemical and biochemical processes takes place in the dough piece during baking under the influence of heat and moisture, which causes considerable changes in the bread dough. These processes cause changes in the baked dough piece, that cause turning the dough into bread. Duration and intensity of the processes occurring on the surface and in the inner layers of the dough piece during baking depend on the temperature. Therefore, creation of optimal modes of heating the baked dough piece at various stages allows you to get products of the required quality. To simulate the processes of crumb formation, changes in temperature inside the dough piece of baking, and specific volume over time with different methods of dough and baking, regression models were used, that take into account the influence of qualitative factors. Each qualitative factor having two grades was replaced by one binary variable. The solution of a multicriteria optimization problem showed that the studied indicators reach the optimal values when baking in an air-o-steam and preparing a dough using hop starter.